ANALISIS PENGARUH INDEPENDENSI AUDITOR EKSTERNAL DAN KARAKTERISTIK PERUSAHAAN TERHADAP KUALITAS LAPORAN KEUANGAN - Rizki Afriandi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
This research aims to determine whether the independence and firm characteristics affect the quality of firm financial statements. The data used in this research was the firm’s financial statement data of manufacturing firms listed on the Indonesian Stock Exchange during the years 2006-2007 with the sampling method using purposive sampling method. The research method used multiple regression analysis method. The result of this research are as follows: (1) the length of auditor-auditee relationship does not significantly influence the quality of financial reporting. (2) firm size significantly influence the qualityof financial reporting. (3) firm age significantly influence the quality of financial reporting. (4) liquidity does not affect the quality of financial reporting. (5) leverage does not affect the quality of financial reporting. (6) investment growth does not affect the quality of financial reporting.